Tolerance aware product development using an enriched hybrid digital mock up. (August 2020) - Friel, Imelda; Butterfield, J.; Robinson, Trevor Thomas; Marzano, Adelaide
Abstract: Current practice in three-dimensional (3D) part construction and product assembly within a digital mock-up (DMU) is based on the nominal sizing of geometry. This approach does not reflect real part dimensions when they are manufactured or the assembly conditions as they come together during the final build. The value of virtual assembly planning (VAP) using clash and gap detection is therefore limited to modeling error identification within the computer-aided design (CAD) domain for nominal conditions only. VAP could become a significantly more powerful tool if the 3D representation of components within the DMU were more representative of 'as manufactured' dimensions. This paper presents the evolution and validation of an enriched DMU (EDMU) introducing the concept of the hybrid assembly which represents components in sizes which can range between upper and lower dimensional limits in addition to the nominally defined form. The resulting capability has been exploited to enable a designer to perform tolerance analysis in the CAD domain in advance of manufacturing planning, allowing tolerance consideration earlier in the design process as the DMU evolves. This has the potential to reduce the time, effort and computational load associated with the application of statistical tolerance analysis by methods engineers later in the product development cycle when the costs associated with change are higher.